The Severity of the COVID-19 Among Chronic Disease Patients in the Selected Hospitals in Riyadh, Saudi Arabia – A Retrospective Study [Letter] - Al-Wathinani AM; Goniewicz K (Risk Management and Healthcare Policy)
Ahmed M Al-Wathinani,1 Krzysztof Goniewicz1,2 1Department of Emergency Medical Services, Prince Sultan Bin Abdulaziz College for Emergency Medical Services, King Saud University, Riyadh, 11541, Saudi Arabia; 2Department of Security, Polish Air Force University, Deblin, PolandCorrespondence: Ahmed M Al-Wathinani, Email ahmalotaibi@ksu.edu.sa